2014
DOI: 10.1007/s00709-014-0690-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional repetitive sequences and fragile sites in chromosomes of Lolium perenne L.

Abstract: Lolium perenne is considered a high-quality forage widely used in temperate regions to meet the shortage of forage during the winter. In this species, some peculiarities related to cytogenetic aspects have already been described, as the variability in number and position of 45S ribosomal DNA (rDNA) sites and the expression of fragile sites, which require further studies to support the understanding of their causes and consequences. In this way, this study aimed to evaluate the relationship between the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
7
14
0
Order By: Relevance
“…This suggests that there is no loss of chromosome fragments in these genotypes. Rocha et al (2016) suggested that the chromatin fiber in FSs of Lolium, Festuca, and Festulolium hybrids have a high decondensation process related to an increased genic activity, thus, supporting the findings by Huang et al (2012), Bustamante et al (2014), and Rocha et al (2015).…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…This suggests that there is no loss of chromosome fragments in these genotypes. Rocha et al (2016) suggested that the chromatin fiber in FSs of Lolium, Festuca, and Festulolium hybrids have a high decondensation process related to an increased genic activity, thus, supporting the findings by Huang et al (2012), Bustamante et al (2014), and Rocha et al (2015).…”
Section: Introductionsupporting
confidence: 75%
“…In interphasic G1 nuclei, the number of 45S signals measured was similar to the descriptions for mitotic chromosomes with six, seven, and four/five sites for L. multiflorum, L. perenne, and F. arundinacea, respectively (Thomas et al, 1996(Thomas et al, , 1997Bustamante et al, 2014;Rocha et al, 2015). In S/G2 nuclei, the number of 45S signals was higher for the three species studied here owing to the occurrence of FSs.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations